Measurement of the CKM angle γ and Bs0-B¯s0 mixing frequency with Bs0→Ds∓h±π±π∓ decays - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen